Improving Sustainable Energy Access among SC/ST Community in Chamarajanagara District of Karnataka - Setty, H. H. Ninga; Dr. Lasya Gopal (IJRDO-Journal of Applied Science, 2020)
The main objective of the project was to improve the indoor air quality among SC&ST households in Chamarajanagara district, Karnataka state, through provision of clean energy solutions for cooking and lighting. This intervention was undertaken by The Energy and Resources Institute (TERI) with the support of Ministry of Science and Technology, Government of India. This pilot intervention comprised enhancing energy access, creating awareness and conducting training programmes and imparting technical know-how on the new technologies to village level energy entrepreneurs and end users of cook stoves and off-grid solutions among the SC/ST community. The project was implemented in six villages in Bhogapura Grama Panchayat (GP) in Chamarajanagara district, Karnataka state, as it is one of the backward districts and has a high SC/ST population. The activities included implementation of 125 integrated domestic energy systems and 300 improved forced draft cook stoves, training of local entrepreneurs / people, stakeholder awareness, user training, establishment of service center, monitoring and assessing the performance of devices and project outcomes etc., assessing the socio-economic status and energy usage of SC/ST households before and post implementation. The improved cook stove resulted in 43.90% savings in fuel wood, which translates into 366.01 tonnes of savings in fuel wood per annum and 669.79 tonnes of CO2 reduction among beneficiary households. In addition, several advantages like faster cooking, less smoke, easy fuel processing, reduction in drudgery for women, reduced health risk for women were observed. Use of solar lights resulted in 40% savings in monthly electricity bill, reduced usage in kerosene (upto 3 litres per month) for lighting, indicating a potential to save an average of 4500 litres of kerosene per annum and reduction of 13.5 tonnes of CO2. Other outcomes included, reduced smoke, relief from eye irritation, and longer duration of light enabled extended study/ work hours. Further, the un-electrified households were able to charge their cell phone batteries. The key learning is that this project provides for a model template for rolling out such programmes in other backward regions/villages in other parts of the country. This paper describes the methodology, socio-economic profile of the project villages, type of activities carried out and impact of the project.